Gigified Knowledge Work: Understanding Knowledge Gaps when Knowledge Work and On-Demand Work Intersect - Wilkins, Denise; Hulikal Muralidhar, Srihari; Meijer, Max; Lascău, Laura; Lindley, Siân (Proceedings of ACM on Human-Computer Interaction, 2022)
Online freelance platforms can transform knowledge work. However, ‘gigification’ also presents challenges, including how freelance workers can access and work with knowledge, which prior research has not examined. Through a qualitative interview study, we identify disparities in how freelancers who work for enterprise companies are able to utilize knowledge as part of their work, when compared with traditional employees of similar organizations. We examine how 38 knowledge workers (21 freelancers, 17 employees) deploy knowledge, work skillfully and mobilize resources to meet knowledge needs. We find that both employees and freelancers understand their own ability to act knowledgeably as a dynamic, collaborative, negotiated and emergent accomplishment. However, for freelancers, the dynamic dimensions of knowledge work - such as helping others see the meaning and value of their work, and creating ties between their work and the enterprise - are only minimally-legitimized and minimally-supported by organizing structures and tools. We present our results as ‘knowledge gaps’, and propose design recommendations to reduce these gaps and consequently make on-demand knowledge work more effective and sustainable.
Article No. 93